Faculty Affairs Committee Meeting Minutes, September 20, 2012 - Faculty Affairs Committee, Valdosta State University Faculty Senate (Valdosta State University Archives and Special Collections, 2012)
Chairperson Tracy Woodard-Meyers; Vice Chairperson Ed Walker; Executive Secretary Diane Holliman; Parliamentarian Aubrey Fowler;
Keywords: Faculty Senate; Faculty Affairs Committee; Valdosta State University; Corporate minutes